Penerapan Jamu Ternak Menggunakan Bahan Alami Kepada Peternak di Dusun Kiera Kabupaten Maluku Barat Daya - Jecklin M. Lainsamputty (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Indonesia's nature has quite high biodiversity, especially plants and is a cultural heritage in utilizing medicinal plants to treat various diseases. This makes many farmers utilize local medicinal plants to be mixed into traditional medicines called livestock herbal medicine. The Community Service Program (PKM) carried out by PSDKU lecturers in the Animal Husbandry Study Program at Pattimura University in West Maluku Regency in collaboration with KKN students through training in making traditional herbal medicine for livestock carried out in Kiera Hamlet, Tounwawan Village, West Maluku Regency. The purpose of implementing this service is to introduce, practice and motivate livestock communities to mix livestock herbal medicine using simple tools and materials available in the surrounding environment. As well as obtaining economic potential in the form of increased income and welfare of livestock communities. The results obtained from this PKM activity were that all participants were very enthusiastic in participating in the intended activity because it was in accordance with the needs of livestock farmers.